Customer Satisfaction in the Banking Industry (Special reference to Vavuniya District) - Selvarajan, P. (University of Sri Jayewardenepura, 2008)
This research study aimed to identify the level of customer satisfaction in different banks in Sri Lanka. The major problem associated with this research study is to identify the leading bank in the industry through customer satisfaction. For this purpose, four banks (two public and two private) have been taken into consideration. This research study consists of a sample of 125 customers from ﬁve variant groups. To measure customer satisfaction, two different structured questionnaires were used to collect data from the banks and the customers. The results show that a Sophisticated Information System plays a key role in the Hatton National Bank, relationship marketing (RM) in the Bank of Ceylon (BOC) and RM and Beneﬁt Schemes together contribute in the People’s Bank and the Commercial Bank of Sri Lanka. Therefore, the HNB is the market leader in the Vavuniya district and the BOC has certain key customers in all categories.
Keywords: Customer Satisfaction; Relationship Marketing; Sophisticated Information Systems; Competitive Advantage; Banking industry; Sri Lanka